Faktor Kunci Dalam Menetapkan Biaya Operasional dan Biaya Investasi di Pondok Pesantren - Rizal Putra, Novit; Ratnaningsih, Sita; Nurochim, Nurochim; Asy'ari, Hasyim; Maftuhah, Maftuhah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Improving the quality of Islamic boarding schools can be illustrated through the effectiveness and cost efficiency of the existing education process. Meanwhile, determining education costs which include operational and investment costs is seen as less effective and efficient, even though these two costs are a guarantee of the quality of education. However, a number of Islamic boarding schools appear to have key factors in determining operational and investment costs within an effective and efficient framework. The aim of this research is to describe the key factors that are effective and efficient in determining operational and investment costs in Islamic boarding schools. The research was carried out at the Al-mukhlishin Islamic boarding school in Ciseeng, Bogor. The research took subjects namely financing managers, educators, school leaders and deputy leaders. A qualitative approach is the choice for data collection techniques, including observational studies, interviews and document studies. There are data analysis steps which are divided into 3, namely: reduction, presentation of findings and verification in the form of conclusions. The research results confirm that operational and investment costs have key factors that must be considered in determining them, namely changes in the student population and increasing educational standards. The implication of the results for education financing managers is that they can consider key factors to be actualized when trying to provide quality education in Islamic boarding schools